Relationship Between Intellectual Capital and Altruism (A Research of Mediterranean Region and Public Sports Organisations) - Arif Özsarı (Selcuk University, 2021)
The present study aims to examine the relationship between intellectual capital and altruism. The research universe consists of personnel working within the public sports organizations located in the Mediterranean Region of Turkey. However, the sample group consists of a total of 363 personnel, 138 women and 225 men, who voluntarily accepted to participate in the research by being selected by convenience sampling method among this personnel. The research data were collected using the "intellectual capital" and "altruism" scales, and confirmatory factor analysis (CFA) was carried out for the related scales. In addition to descriptive statistics, correlation and regression methods were applied within the scope of the relational model in the research. According to the result of the correlation analysis, a significant, positive, but low-level correlation was found between human capital, social capital, and structural capital, which are among the sub-dimensions of intellectual capital, and altruism. According to the result of multiple regression analysis, it can be noted that structural capital, which is the sub-dimension of intellectual capital, has a significant positive contribution to explaining the impact of intellectual capital on altruism. As the level of intellectual capital (structural capital) of those who work in public sports organizations increases, their altruism will also increase.